Effects of varieties and inorganic fertilizers on growth and flowering of gerbera (Gerbera jamesonii) - M. H. Rashid (Journal of Agriculture, Food and Environment)
An experiment was conducted at the Landscaping Section of the Department of Horticulture, Bangladesh Agricultural University, Mymensinghduring the period from November 2017 to May 2018 to investigate the effect of varieties and inorganic fertilizers on growth and flowering of gerbera. The experiment consisted of two factors viz., Factor A: varieties (V1=Mini Daisy, V2= Aladin) and FactorB: Different levels of inorganic fertilizers (T0= 0, T1 = N 300 kg/ha, T2= P 275 kg/ha, T3= K 225 kg/ha, T4= N+P+K 300+275+225 kg/ha). The experiment was laid out in Randomized Complete Block Design with three replications. Varieties and different levels of inorganic fertilizers had significant effect on plant height, number of leaves per plant, spread of leaves, days to first flower bud emergence, days to harvest maturity, total number of flowers produced and spread of flowers and field life of gerbera. Total number of flowers per plant (10.89) was recorded from Aladin (V2), which was higher than that of Mini Daisy (V1) (10.16). The highest number of flowers per plant (12.44), while, the lowest number of flowers (9.10) was obtained fromT0(control). Considering the combined effect,the maximum number of flowers per plant (12.87) was obtained from the treatment combination of V2T4(Aladin+N+P+K), while, the lowest number of flowers per plant (8.67) was recorded from V1T0(Control). Therefore, combined application of N, P and Kfertilizers along with variety Aladin was found to be better in respect of growth and flowering of gerbera.